KOMODIFIKASI FILM CRITICAL ELEVEN: Studi Deskriptif Tentang Komodifikasi Ekonomi Politik Film Critical Eleven - Pundra Rengga Andhita (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2018)
As technology advances, film is packaged not only as entertainment. Inevitably, the film has become a commodity of the media industry. The existence of film as one medium of communication can be an effective channel for people to consume the message content in accordance with the will of the maker. Currently very easy to find various films that presents the diversity of themes with stories that attract the attention of the public. One of them is the movie "Critical Eleven" production from Starvision Plus and Legacy Pictures directed by Monty Tiwa. In the perspective of communication science, film is a mass media instrument containing the political economy of media value. The film can be placed as a commodity that can be traded in the market. One expert who has concentration on this study is Vincent Mosco. In his explanation, Mosco explains there are three things that can be considered in the political economy of media that is commodification, spatialization and structuring. So from Mosco's understanding, this research will further describe the commodification in the Critical Eleven film.Key Words: Commodification, Political Economy, Film, Critical Eleven